2022
DOI: 10.1002/poc.4331
|View full text |Cite
|
Sign up to set email alerts
|

Ligand effect on the stability, reactivity, and acidity of imidazolium systems

Abstract: Imidazolium and its different N‐substituted derivatives are considered in this study to investigate their stability, reactivity, and acidity. Different aliphatic and aromatic ligands have been introduced in imidazolium to see their effect. It has been observed that the acidity of imidazolium systems increases with ligands having higher electron‐withdrawing nature. The studied systems are found to be weak acids, and weak bases can generate the corresponding carbene systems. The stability, reactivity, and aromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Aromaticity is an important factor that offers stability to the system and so to check this property before and after Li doping and H 2 adsorption we studied NICS (0,1) (nucleus independent chemical shift) [20,[56][57][58][59][60][61] and we also determined NBO (natural bonding orbital) charges [19][20] to know the order of changes of charge after gradual H 2 adsorption. Calculations were made on gravimetric wt% [19][20][21] to cross-check with the U.S.DOE target [22] by considering the following Equation (3):…”
Section: Theory and Computational Detailmentioning
confidence: 99%
“…Aromaticity is an important factor that offers stability to the system and so to check this property before and after Li doping and H 2 adsorption we studied NICS (0,1) (nucleus independent chemical shift) [20,[56][57][58][59][60][61] and we also determined NBO (natural bonding orbital) charges [19][20] to know the order of changes of charge after gradual H 2 adsorption. Calculations were made on gravimetric wt% [19][20][21] to cross-check with the U.S.DOE target [22] by considering the following Equation (3):…”
Section: Theory and Computational Detailmentioning
confidence: 99%
“…Das 11 examined stability, reactivity, and aromaticity of imidazolium by using CDFT approach. Authors found that ligands with a stronger electron‐withdrawing nature cause imidazolium complexes to evolve into more acidic.…”
mentioning
confidence: 99%